Proposal of neural network model for neurocognitive rehabilitation and its comparison with fuzzy expert system model - Kotyrba, Martin; Habiballa, Hashim; Volna, Eva; Jarusek, Robert; Smolka, Pavel; Prasek, Martin; Malina, Marek; Jaremova, Vladena (BMC medical informatics and decision making, 2023)
This article focuses on the development of algorithms for a smart neurorehabilitation system, whose core is made up of artificial neural networks. The authors of the article have proposed a completely unique transfer of ACE-R results to the CHC model. This unique approach allows for the saturation of the CHC model domains according to modified ACE-R factor analysis. The outputs of the proposed algorithm thus enable the automatic creation of a personalized and optimized neurorehabilitation plan for individual patients to train their cognitive functions. A set of tasks in 6 levels of difficulty (level 1 to level 6) was designed for each of the nine CHC model domains. For each patient, the results of the ACE-R screening helped deter-mine the specific CHC domains to be rehabilitated, as well as the initial gaming level for rehabilitation in each domain. The proposed artificial neural network algorithm was adapted to real data from 703 patients. Experimental outputs were compared to the outputs of the initially designed fuzzy expert system, which was trained on the same real data, and all outputs from both systems were statistically evaluated against expert conclusions that were available. It is evident from the conducted experimental study that the smart neurorehabilitation system using artificial neural networks achieved significantly better results than the neurorehabilitation system whose core is a fuzzy expert system. Both algorithms are implemented into a comprehensive neurorehabilitation portal (Eddie), which was supported by a research project from the Technology Agency of the Czech Republic.
Keywords: Neural network model; algoritmy; neurorehabilitace; Fuzzy expert system model; ACE-R; lidé; Neural Networks, Computer; Neurological Rehabilitation; fuzzy logika; CHC; Neurocognitive rehabilitation; expertní systémy; Algorithms; Fuzzy Logic; neuronové sítě; Expert Systems; Humans